Model Strategi Prosedur Penyusunan Paket Wisata di PT Bali Daksina Wisata Tour and Travel - Januri, Yohanes Kelfin; Pramana Putra, Putu Guntur; Prayogi, Putu Agus; Wijaya, I Gusti Agung Rendra (Fakultas Bisnis dan Pariwisata, 2024)
Tourism involves travelling using the services of a travel agent. Increased tourist visits have a positive impact on the country by opening up opportunities for travel agents to sell their services. PT Bali Daksina Wisata Tour and Travel, as one of the travel agents, offers tirtayatra tour packages as well as inbound and outbound tour packages. This study aims to determine the procedure for preparing tour packages at PT Bali Daksina Wisata, the obstacles experienced in preparing packages, and the strategies applied to overcome these obstacles. Data were collected through observation, interviews, and documentation studies, then analysed through data reduction, data presentation, and conclusion drawing. PT Bali Daksina Wisata Tour and Travel faces several obstacles in preparing tour packages, such as lack of innovation, market competition, lack of relationships, tourist destinations that are not yet well known, inadequate locations and parking lots. To overcome these obstacles, the company needs to add attractions that are currently popular and promote them through social media. Consistency in product, price, and tour package innovation is important to face competition. Building stronger relationships will help fulfil consumer needs and better engagement with those in lesser-known tourist destinations can make it easier to book accommodation. Providing dedicated parking spaces for employees and guests will also increase convenience and improve customer satisfaction.